2019
DOI: 10.1044/2019_aja-18-0173
|View full text |Cite
|
Sign up to set email alerts
|

Variations Within Normal Hearing Acuity and Speech Comprehension: An Exploratory Study

Abstract: Purpose Many young adults with a mild hearing loss can appear unaware or unconcerned about their loss or its potential effects. A question that has not been raised in prior research is whether slight variability, even within the range of clinically normal hearing, may have a detrimental effect on comprehension of spoken sentences, especially when attempting to understand the meaning of sentences that offer an additional cognitive challenge. The purpose of this study was to address this question. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…Difficulties within language and flexibility have previously been identified as risk factors impacting ODD in TD boys, whereas only flexibility was identified as a risk factor in TD girls (Kerekes et al, 2014). As elasticity is a measure of flexibility and auditory acuity is associated with speech comprehension (Lee et al, 2018;Ayasse et al, 2019), our results are in line with previous research as far as the male correlations go. However, in the female group, a higher performance in visual flexibility is associated with ODD rather than a lower performance.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Difficulties within language and flexibility have previously been identified as risk factors impacting ODD in TD boys, whereas only flexibility was identified as a risk factor in TD girls (Kerekes et al, 2014). As elasticity is a measure of flexibility and auditory acuity is associated with speech comprehension (Lee et al, 2018;Ayasse et al, 2019), our results are in line with previous research as far as the male correlations go. However, in the female group, a higher performance in visual flexibility is associated with ODD rather than a lower performance.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with our hypothesis of ASD females showing the same unisensory processing advantage in social communication as is seen in previous studies of TD women (McGivern et al, 2019;Siedlecki et al, 2019;Thornton et al, 2019). Auditory Acuity has previously been associated with language comprehension (Lee et al, 2018;Ayasse et al, 2019) so, a process such as language, heavily relying on auditory information will naturally be favored by those having a superior auditory processing. However, in the male group, a better performance in Auditory Acuity was associated with less rated problems of ODD (r = −0.613, p = 0.005; Figure 2), which is in line with our hypothesis of males having a superior visual processing blocking out auditory information.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, we found a significant relationship between hearing thresholds and ERP amplitudes in the RRC paradigm. A study by Ayasse et al ( 2019 ) found that even in young adults who pass a screen for normal hearing, slightly elevated hearing thresholds detrimentally affected processing of difficult syntactic constructions. This suggests that it is important to consider hearing thresholds as continuous variables rather than considering people within certain threshold ranges as homogeneous groups.…”
Section: Discussionmentioning
confidence: 99%
“…First, we chose peripheral hearing loss as measured by hearing thresholds. Hearing loss is highly prevalent in older adults—approximately 20% at age 60 and 50% at age 70 (Goman and Lin, 2016 ; Bisgaard and Ruf, 2017 ; Mick et al, 2019 )—and hearing thresholds have been shown to influence many behavioral results in previous studies (Wingfield et al, 2006 ; DeCaro et al, 2016 ; DeDe and Flax, 2016 ), even in young adults (Ayasse et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%